2011
DOI: 10.1371/journal.pntd.0001440
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Incompatibility as a Means of Controlling Culex pipiens quinquefasciatus Mosquito in the Islands of the South-Western Indian Ocean

Abstract: The use of the bacterium Wolbachia is an attractive alternative method to control vector populations. In mosquitoes, as in members of the Culex pipiens complex, Wolbachia induces a form of embryonic lethality called cytoplasmic incompatibility, a sperm-egg incompatibility occurring when infected males mate either with uninfected females or with females infected with incompatible Wolbachia strain(s). Here we explore the feasibility of the Incompatible Insect Technique (IIT), a species-specific control approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
61
0
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 72 publications
3
61
0
5
Order By: Relevance
“…Second, Wolbachia -induced CI could also be used as a spreading/replacement mechanism for desired phenotypes, because infected females have a reproductive advantage over uninfected females, since they can mate with both uninfected and infected males thus invading populations in nature (Bourtzis, 2008; Bourtzis and Robinson, 2006; Bourtzis and O’Neill, 1998; Brelsfoard and Dobson, 2009; Dobson et al, 2002; Hoffmann et al, 1998; Rasgon, 2008, 2007; Sinkins and Gould, 2006). Wolbachia -based suppression and/or replacement approaches have been documented with insect vector species (the mosquito species: Culex pipiens species complex, Aedes aegypti , Aedes albopictus ) under laboratory, semi-field or field conditions (Atyame et al, 2011; Chambers et al, 2011; Hoffmann et al, 2011; Laven, 1967; Ruang-Areerate and Kittayapong, 2006; Walker et al, 2011; Xi et al, 2005). Most of the above-mentioned examples were based on host transinfection via embryonic cytoplasmic injections.…”
Section: Wolbachia-induced CI and Tsetse Fliesmentioning
confidence: 99%
“…Second, Wolbachia -induced CI could also be used as a spreading/replacement mechanism for desired phenotypes, because infected females have a reproductive advantage over uninfected females, since they can mate with both uninfected and infected males thus invading populations in nature (Bourtzis, 2008; Bourtzis and Robinson, 2006; Bourtzis and O’Neill, 1998; Brelsfoard and Dobson, 2009; Dobson et al, 2002; Hoffmann et al, 1998; Rasgon, 2008, 2007; Sinkins and Gould, 2006). Wolbachia -based suppression and/or replacement approaches have been documented with insect vector species (the mosquito species: Culex pipiens species complex, Aedes aegypti , Aedes albopictus ) under laboratory, semi-field or field conditions (Atyame et al, 2011; Chambers et al, 2011; Hoffmann et al, 2011; Laven, 1967; Ruang-Areerate and Kittayapong, 2006; Walker et al, 2011; Xi et al, 2005). Most of the above-mentioned examples were based on host transinfection via embryonic cytoplasmic injections.…”
Section: Wolbachia-induced CI and Tsetse Fliesmentioning
confidence: 99%
“…IIT has been successfully developed for some major agricultural pests 48,49 and recently has also been explored for its effectiveness in the control of mosquito populations in the field. Recently, Atyame and collaborators 50 showed that the wPip(Is) Wolbachia strain, naturally infecting Culex pipiens pipiens from Turkey, can be used in the context of IIT to sterilize Cx. p. quinquefasciatus females from several islands of the southwestern Indian Ocean, confirming the feasibility of IIT in mosquito control.…”
mentioning
confidence: 99%
“…Infection with Wolbachia has been reported in many species, including some disease vectors such as Aedes albopictus and Culex quinquefasciatus ( =  Cx. pipiens fatigans ) [15], [21], [30]. For naturally uninfected insects, artificial Wolbachia infection would generate an incompatible strain that could be used to suppress target populations [28].…”
Section: Discussionmentioning
confidence: 99%
“…Wolbachia -infected mosquito strains that display novel patterns of CI for population suppression are usually created by introgression or transinfection [30][32]. The preparation of incompatible mosquitoes using such methods is often laborious and time-consuming.…”
Section: Introductionmentioning
confidence: 99%